1997
DOI: 10.1002/(sici)1097-4679(199704)53:3<243::aid-jclp7>3.0.co;2-s
|View full text |Cite
|
Sign up to set email alerts
|

Optimism, social support, and premenstrual dysphoria

Abstract: The relationships between dispositional optimism, social support, and mood and performance symptoms associated with the premenstrum were examined in a sample of 101 adult women. Optimism and satisfaction with one's level of social support were positively correlated. Optimism was related inversely to mood-related symptoms, even after controlling for the effects of social support. Optimism did not correlate with premenstrual performance impairment. Social support did not correlate with any premenstrual symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
7
0
2

Year Published

2002
2002
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 12 publications
2
7
0
2
Order By: Relevance
“…More optimistic patients may be more likely to discuss their cancer because they anticipate greater receptivity from potential disclosure targets and have more disclosure-oriented attitudes. Optimistic subjects report more satisfying levels of social support (e.g., Fontaine and Seal, 1997), and may already have in place interpersonal communication pathways characterized by relatively high levels of collaboration and trust. Recent evidence also suggests that optimism may be associated with decreased cancer mortality (Schultz et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…More optimistic patients may be more likely to discuss their cancer because they anticipate greater receptivity from potential disclosure targets and have more disclosure-oriented attitudes. Optimistic subjects report more satisfying levels of social support (e.g., Fontaine and Seal, 1997), and may already have in place interpersonal communication pathways characterized by relatively high levels of collaboration and trust. Recent evidence also suggests that optimism may be associated with decreased cancer mortality (Schultz et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Social support influences optimism by providing emotional support and relationships that offer acceptance and guidance. Researchers have found positive relationships between social support and optimism in women aged 16 to 45 (Fontaine & Seal, 1997) and in men with an average age of 38 (Park & Folkman, 1997). Based on theory and research, the fifth hypothesis predicted that there would be a positive relationship between social support and optimism in middle-age adults.…”
Section: Purposementioning
confidence: 99%
“…It has been theorized that optimists are more socially attractive than pessimists, and consequently they are more likely to be integrated into supportive social networks, and to receive favorable responses from their social environment (e.g., Scheier & Carver, 1987). Various studies have shown a positive relationship between optimism and perceived available social support, such as the availability of helpful others (e.g., Brissette, Scheier, & Carver, 2002;Fontaine & Seal, 1997;Trunzo & Pinto, 2003), and received social support, such as the frequency of helpful interactions (Aspinwall & Taylor, 1992).…”
Section: Introductionmentioning
confidence: 99%